PENGGUNAAN METODE TOPSIS DAN METODE ELECTRE SEBAGAI PERBANDINGAN HASIL KEPUTUSAN PEMILIHAN LOKASI LAHAN TAMBAK PALING TERBAIK UNTUK DIJADIKAN USAHA TAMBAK AIR PAYAU - Yani Maulita; Katen Lumbanbatu; Akim M. H. Pardede; Farid Reza Malau (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2018)
The number of methods available on the decision support system so that sometimes confuse choosing which match the use of methods appropriate to the case of decision support systems. For this reason, a comparison of the best decision-making systems for pond ponds to be used for brackish water ponds for comparison of decision results is made. The method used is Topsis Method and Electre method by determining the number of criteria, type of criteria (Cost and Benefit), with 3 alternatives. The result of the research is the result of manual calculation same with the calculation that exist in system. Each calculation of the Topsis method and the Electre method indicates that the result of the best choice of pond location location to be used as brackish water bracket of each suna Regency method has different end result. Based on the calculation of the use of Topsis method found in the village of Kabukico is the best alternative for building brackish water ponds with a value of 0.5711. While Based on the results of calculation of Electre method found in Duton Batu Village is the highest alternative because Duton Batu Village has 2 elements that are true.